FACTORS RELATED TO WORK FRUSTRATION ON THE HEALTH OF EMPLOYEES IN CENTRAL LOMBOK IN 2023 - Raodatul Jannah; Adam Hernawan (Jurnal Health Sains, 2023)
The rapid development of science and technology and education also brings changes in human life. These changes have the effect of higher demands on each individual to further improve their performance. In order for their existence to be maintained, each individual will experience stress and frustration, especially for individuals who are less able to adjust to these developments. If you pay attention to people in everyday life, you will see various things that happen among the community. Some always seem to be happy, happy, happy and laughing even though what they will face later is different as expected. There are also those who often complain and grieve, despair, give up, do not fit in with other people and their work. This makes a person experience a health problem. This happens because of the lack of community for something to maintain harmony in society. It is these disturbing symptoms that prompt psychiatrists to try to investigate what causes different people's behaviors, despite the same conditions. This effort fostered one of the youngest branches of psychology, health. And in studying health, there are stress disorders and frustration among the community, due to a person cannot control himself to be better.